2008
DOI: 10.4489/myco.2008.36.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Physiological Studies on Soil Fungi at Western Region, Libya

Abstract: Sixty three species and 5 varieties belonging to 30 fungal genera were collected from 75 soil samples. Cultivated (29 genera and 58 species + 5 var.), desert (22 and 35 + 2 var.) and saline soil (21 and 41 + 1 var.) fungi were recovered on glucose-, cellulose- and 50% sucrose-Czapek's agar at 28℃. The most common genera were Alternaria, Aspergillus, Emericella, Fusarium, Mycosphaerella, Nectria and Penicillium. The most prevalent species from the three types of soils on the three types of media were Alternaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
3
18
2
Order By: Relevance
“…T. reesei, 38 Talaromyces verruculosus, 39 and Chaetomium globosum. 40 It was reported that good CMCase activity was observed with Penicillium funiculosum (pH 4.82), Penicillium citrinum (pH 5.5), Penicillium chrysogenum (pH 5.0), and Aspergillus niger (pH 5.0). [41][42][43][44] As reported, lamentous fungi have reasonably good growth over a broad range of pH 2-9, with an optimal range of 3.8 to 6.0.…”
Section: Optimization Of the Conditions For The Cellulase Productionmentioning
confidence: 99%
“…T. reesei, 38 Talaromyces verruculosus, 39 and Chaetomium globosum. 40 It was reported that good CMCase activity was observed with Penicillium funiculosum (pH 4.82), Penicillium citrinum (pH 5.5), Penicillium chrysogenum (pH 5.0), and Aspergillus niger (pH 5.0). [41][42][43][44] As reported, lamentous fungi have reasonably good growth over a broad range of pH 2-9, with an optimal range of 3.8 to 6.0.…”
Section: Optimization Of the Conditions For The Cellulase Productionmentioning
confidence: 99%
“…The preference for acidic pH for production of cellulase and other lignocellulose degrading enzymes has been reported for most cellulase producing ascomycetes fungi e.g. T. reesei [23], A. cellulolyticus [24], and C. globosum [25]. This preference is related to pH for optimal growth and catalytic activity of the enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…*OR= Occurrence remarks: H = high occurrence from 6-10 cases, M = moderate occurrence from 3-5cases, L= low occurrence 2 cases and R = rare occurrence 1 case. with different numbers and frequencies from various soils in many places of the world by several workers (Abdel-Hafez et al, 1990;Moubasher and Mazen, 1991;Abdel-Hafez, 1994;Karl andIain, 2004 andSaleem, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the optimum pH for cellulase production was 6 to 7 and optimum temperature was about 40°C. El Said and Saleem (2008) found that maximum production of endo-ß-1,4 glucanase by Cheatomium globosum was achieved 6 days after incubation at 30°C with incorporation of maltose as carbon source and NH 4 NO 3 as nitrogen source in the culture medium which is initially adjusted to pH 6. Recently Saleem et al (2013) found that maximum production of exo-and endo-ß-1,4 glucanase by Mucor circinelloides and A. flavus was achieved 6 days after incubation at 30°C with incorporation of fructose or sucrose as a sole carbon source and potassium nitrate or sodium nitrate as a sole nitrogen source, respectively in the basal medium initially adjusted to pH 6.…”
Section: Cellulolytic Activities Of Some Fungal Isolatesmentioning
confidence: 99%
See 1 more Smart Citation